PENGARUH HARGA DAN PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA ROCKET CHICKEN JEPUN TULUNGAGUNG - Edial Nanang Setiawan (Jurnal Riset Multidisiplin Edukasi, 2026)
This study is motivated by the increasing number of visitors to Rocket Chicken Jepun Branch, Tulungagung, particularly during Ramadan until after the Eid al-Fitr holiday in 2024. In the context of intense competition in the fast-food industry, price and service are two important factors presumed to influence customer satisfaction. This research aims to examine the effect of price and service on customer satisfaction. The study employs a quantitative method using a multiple linear regression approach. The research sample consists of 100 respondents selected through purposive sampling, with criteria of being at least 18 years old and having made a minimum of two purchases. Data analysis was conducted using SPSS, including validity and reliability tests, t-test, F-test, and coefficient of determination (R²). The results indicate that both price and service have a positive and significant effect on customer satisfaction, both partially and simultaneously. The R² value of 0.462 indicates that price and service explain 46.2% of the variation in customer satisfaction. The study concludes that competitive pricing strategies and excellent service are key factors in building customer satisfaction in the fast-food industry.